2017
DOI: 10.21767/2049-5471.1000107
|View full text |Cite
|
Sign up to set email alerts
|

Women Living with HIV in India: Looking up from a Place of Stigma, Identifying Nexus Sites for Change

Abstract: Current knowledge• For people living with HIV infection in India, stigma is a pervasive reality and the greatest barrier to accessing treatment, quality of life and survival.• However, women and men experience stigma differently. Despite typically contracting the disease through marital sexual relations, married monogamous women are also subject to stigma resulting from moral blame.• Stigma affects women both in public spheres of social relationships and in private through psychological stresses. These spheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…High prevalence of depression has consistently been documented among PLH in India [ 3 8 ]. The few studies that have examined gender differences in depression among PLH in India have found higher prevalence and severity of depression among women than men [ 9 , 10 ]. However, previous studies on HIV and mental health in India have included small samples of PLH (n < 100), which limit meaningful comparisons between men and women.…”
Section: Introductionmentioning
confidence: 99%
“…High prevalence of depression has consistently been documented among PLH in India [ 3 8 ]. The few studies that have examined gender differences in depression among PLH in India have found higher prevalence and severity of depression among women than men [ 9 , 10 ]. However, previous studies on HIV and mental health in India have included small samples of PLH (n < 100), which limit meaningful comparisons between men and women.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-related stigma is a known barrier to treatment adherence among PLWH (Katz et al, 2013), but the unique context in which this population experiences stigma necessitates a comprehensive approach to understanding how it influences all facets of health. In a recent article about women living with HIV in India, Short and Vissandjée (2017) assert that Engel’s biopsychosocial model was well-positioned to assess HIV-related stigma because stigma was manifest in all aspects of one’s life. Our findings support this assertion.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports a study from India, which showed accessing treatment, quality of life and survival were affected by stigma among women living with HIV infection. 13 …”
Section: Discussionmentioning
confidence: 99%